A Family of Gradient Descent Grid Frequency Estimators for the SOGI Filter - Matas, Jose; Martin, Helena; de la Hoz, Jordi; Abusorrah, Abdullah; Al-Turki, Yusuf A.; Al-Hindawi, Mohammed (IEEE transactions on power electronics, 2018)
This paper applies the adaptive gradient descent method to the second-order generalized integrator (SOGI) filter in order to find an online estimation algorithm for the grid frequency, which leads to the proposal of three possible estimators. One of them is identical to the frequency-locked loop algorithm reported in the literature, which proves that it should be understood as a gradient descent estimation algorithm and not as a "frequency locked loop." The proposed gradient descent estimators are simple and suitable to be implemented into a digital processor with small computational burden. However, due to the SOGI characteristics, the estimators show to be especially sensitive to subharmonic and dc-offset voltage distortion. These problems are removed adopting a cascaded double SOGI approach, which strongly increases the rejection capability to harmonics and enhances the response to voltage sags. Simulation and experimental results are provided to validate the proposed contribution.